CRITICAL ANALYSIS ON VALIDATION OF A NEW METHOD FOR DETECTING MICROBIAL RESISTANCE TO ANTIBIOTICS IN CLINICAL SPECIMENS - HAMAD OWAYDHAH SALEH ALRABIE, SALEM ALI ALMUHAYD, MOHAMMED YHAYA ALSHIBAN, JAFAR HASSAN MOHAMMED ALMAKRAMI, IBRAHIM MOHAMMED NASSER AL ZARAR, YOUSSEF MUHAMMAD NASSER AL ZAARAR, NASSER SALEM ALI AL KHURAYM, BADIE DIFALLAH QASSIM AL MASHHAM (Chelonian Research Foundation, 2022)
Validation of new means of microbial resistance to antibiotics in clinical specifications is essential for the appropriate and timely diagnosis of infections. This paper takes a critical look at the validation steps involved in interpreting such methods, highlighting the key aspects and difficulties they pose as well as impacting clinical practices. This study, through a review of adequate literature and research, intends to demonstrate the indispensability of a foolproof validation process in improving the performance and applicability of antimicrobial resistance testing techniques. Keywords: validation information, microbial resistance, drug selection, clinical specimens, diagnosis, and treatment.